2011
DOI: 10.1029/2011je003866
|View full text |Cite
|
Sign up to set email alerts
|

Lunar surface rock abundance and regolith fines temperatures derived from LRO Diviner Radiometer data

Abstract: [1] Surface temperatures derived from thermal infrared measurements provide a means of understanding the physical properties of the lunar surface. The contrasting thermophysical properties between rocks and regolith fines cause multiple temperatures to be present within the field of view of nighttime multispectral data returned from the Lunar Reconnaissance Orbiter (LRO) Diviner Radiometer between 60°N/S latitudes. Regolith temperatures are influenced by the presence of rocks in addition to factors such as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
385
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 282 publications
(435 citation statements)
references
References 31 publications
22
385
0
2
Order By: Relevance
“…Rock abundance derived in this way represents the fractional area of exposed rocks large enough to be thermally isolated from the surrounding regolith, larger than~10-100 cm in size (section 3.3.1; cf. Bandfield et al, 2011). Thus, rocks smaller than~10 cm augment the derived regolith temperatures and are considered part of the regolith in the study reported here.…”
Section: Data Setmentioning
confidence: 99%
See 4 more Smart Citations
“…Rock abundance derived in this way represents the fractional area of exposed rocks large enough to be thermally isolated from the surrounding regolith, larger than~10-100 cm in size (section 3.3.1; cf. Bandfield et al, 2011). Thus, rocks smaller than~10 cm augment the derived regolith temperatures and are considered part of the regolith in the study reported here.…”
Section: Data Setmentioning
confidence: 99%
“…Previous work indicated that rock abundance is a key indicator of crater age (Bandfield et al, 2011;Ghent et al, 2014). Ghent et al (2014) demonstrated that a quantitative relationship exists between the 95th percentile rock abundance within a crater's ejecta blanket and its model age based on counts of superposed craters.…”
Section: Impact Craters and Ejectamentioning
confidence: 99%
See 3 more Smart Citations